Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/universe8110556
|View full text |Cite
|
Sign up to set email alerts
|

WKB Approaches to Restore Time in Quantum Cosmology: Predictions and Shortcomings

Abstract: In this review, we analyse different aspects concerning the possibility to separate a gravity-matter system into a part which lives close to a quasi-classical state and a “small” quantum subset. The considered approaches are all relying on a WKB expansion of the dynamics by an order parameter and the natural arena consists of the Bianchi universe minisuperspace. We first discuss how, limiting the WKB expansion to the first order of approximation, it is possible to recover for the quantum subsystem a Schrödinge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 184 publications
(376 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, it was shown that the cases (g + = 1, g − = 0) and (g + = 0, g − = 1) correspond to an extension of general relativity that includes solutions corresponding to an additional effective pressureless perfect fluid matter source. Interestingly, such a matter source has been of prior interest as a possible solution to the problem of time in quantum gravity [25,27,[30][31][32]. We find it encouraging that in the present models, the perfect fluid arises 'naturally' from the theory and does not have to be independently posited.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, it was shown that the cases (g + = 1, g − = 0) and (g + = 0, g − = 1) correspond to an extension of general relativity that includes solutions corresponding to an additional effective pressureless perfect fluid matter source. Interestingly, such a matter source has been of prior interest as a possible solution to the problem of time in quantum gravity [25,27,[30][31][32]. We find it encouraging that in the present models, the perfect fluid arises 'naturally' from the theory and does not have to be independently posited.…”
Section: Discussionmentioning
confidence: 58%
“…This is the so-called reduced phase space quantisation (RPSQ) that is the most straightforward procedure since it is an exact algorithm requiring no WKB approximation based on the wave function of the Universe, even if the Hamiltonian density can be non-local. The second one is achieved by implementing both the WKB and Born-Oppenhaimer approximations, namely, the Vilenkin approach, for details see [21,22].…”
Section: Schrödinger Dynamics Of Bianchi I Modelmentioning
confidence: 99%
“…a physical clock is constructed via an internal gravity or matter degree of freedom [18]. Some examples of how to construct a time variable for the quantum gravity dynamics via a specific field are [19][20][21]23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are physical settings, both in early cosmology and for the gravitational collapse, in which the background metric cannot be regarded as a purely classical dynamics, but simply an essentially classical dynamics affected by quantum fluctuations of the geometry. This line of research has been till now developed by a relatively limited number of studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], in which the first problem to be addressed is the emergence of a time variable for QFT from the gravity-matter Wheeler-DeWitt equation.…”
Section: Introductionmentioning
confidence: 99%